Problem-Based Learning : What do we know about it today? - SHKARIN, V. V; Fedorova, Olga V.; Marina, Kapitonova; Norhida, Ramli; Saiful Bahri, Talip; Brohi, I. B.; UDOCHKINA, L. A.; Gupalo, Sergey P. (Avicenna Tajik State Medical University, National Academy of Sciences of Tajikistan, 2025)
Objective: To evaluate the awareness of problem-based learning (PBL) among academic staff in Russian medical universities' Basic Medical Sciences departments. This assessment was conducted using a standardized, partially modified questionnaire. Additionally, the study aimed to explore the faculty's readiness to implement PBL in their curriculum within their departments. Methods: A total of 268 faculty members from the Basic Medical Sciences departments participated in a survey designed to assess their level of awareness and engagement with PBL as a modern educational approach. The survey data were analyzed using Statistica 10 software, employing statistical methods such as the chi-squared (χ²) test, with a significance level set at p<0.05. Results: The analysis indicated that faculty members at Russian medical universities generally possessed a relatively high level of awareness regarding PBL (72%). This awareness was significantly associated with various factors: gender (p<0.05, with higher awareness in women), age (p<0.01, peaking among those aged 41-50), academic degree (p<0.05, being highest among PhD holders), and teaching experience (p<0.01, most prevalent in lecturers with 5-10 years of experience). However, awareness was not shown to be related to academic position. However, only a few lecturers received formal training in PBL (21%), and fewer implemented the obtained skills in their teaching practices (46%). The level of knowledge about PBL among respondents was categorized as high, medium, and low in 7.6%, 45.8%, and 46.5%, respectively. Knowledge levels were associated with age (p<0.05) but not with other socio-demographic or professional factors. Conclusion: The collected data can identify faculty members best prepared to participate in the pilot project introducing PBL in Russian medical schools’ curricula.